(untitled) (Informatica, 2019)
Big data generated in different domains and industries are voluminous and the velocity at which they are generated is pretty high. While research works carried out continuously to handle big data is at one end, processing it to develop the business insights is a hot topic to work on the other end. Though there are lot of technologies and tools developed to handle big data and extract insights from them, there are lot of challenges and open issues that are yet to be addressed. This paper presents an overview on predictive analytics with big data. The overview throws light on the scope of predictive analytics for big data and the contemporary works done in several domain sectors using dierent technologies. This paper categorizes the major technical challenges of predictive analytics on big data under six headings. The paper concludes with the identification of open issues and future directions to work on for researchers in this field.